49.4k views
4 votes
A(x+b)=g+3f

solve for x

1 Answer

4 votes

Answer:


x = ((g + 3f)/(a)) - b

Explanation:

Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

Note that PEMDAS =

Parenthesis

Exponents

Multiplication

Division

Addition

Subtraction

& is the order of operation.

First, divide a from both sides:


a(x + b) = g + 3f


(a(x + b))/(a) = (g + 3f)/(a)


x + b = (g + 3f)/(a)

Next, subtract b from both sides to isolate the variable, x.


x + b (-b) = (g + 3f)/(a) (-b)


x = ((g + 3f)/(a)) - b


x = ((g + 3f)/(a)) - b

User Jomahony
by
4.8k points